Principal Purpose Test (PPT) As An Instrument To Detect Tax Treaty Abuse - Akbar Saputra; Muchamad Irham Fathoni (Pelopor Publikasi Akademika, 2023)
Using descriptive qualitative method, this paper collects various references and literary sources regarding tax treaty abuse and policy recommendations that can be implemented to prevent tax treaty abuse, one of which is using Principal Purpose Test (PPT). Besides, this paper also explains Indonesia’s current tax regulations regarding PPT, as well as learns how other country like Australia could implement PPT into its own domestic tax regulations. From our discussion, it can be concluded that Organization for Economic Co-operation and Development (OECD) has recommended a series of policies to prevent tax treaty abuse, i.e. Multilateral Instrument in the form of General Anti-Abuse Rule (GAAR), which include PPT and other optional policies combined like Limitation on Benefit. Through Director General of Taxes Regulation Number PER-25/PJ/2018, Indonesia has actually started to implement PPT into domestic tax regulations, even though it is not as strict and complex as those of Australia, through its tax authority, Australia Tax Office (ATO). ATO, using PSLA 2019/D2, has also implemented step-by-step procedures to handle cases indicated to be related with tax treaty abuse